Calpain-1 regulates platelet function in a humanized mouse model of sickle cell disease. Issue 160 (December 2017) - Nwankwo, Jennifer O.; Gremmel, Thomas; Gerrits, Anja J.; Mithila, Farha J.; Warburton, Rod R.; Hill, Nicholas S.; Lu, Yunzhe; Richey, Lauren J.; Jakubowski, Joseph A.; Frelinger, Andrew L.; Chishti, Athar H.
Abstract: One of the major contributors to sickle cell disease (SCD) pathobiology is the hemolysis of sickle red blood cells (RBCs), which release free hemoglobin and platelet agonists including adenosine 5′-diphosphate (ADP) into the plasma. While platelet activation/aggregation may promote tissue ischemia and pulmonary hypertension in SCD, modulation of sickle platelet dysfunction remains poorly understood. Calpain-1, a ubiquitous calcium-activated cysteine protease expressed in hematopoietic cells, mediates aggregation of platelets in healthy mice. We generated calpain-1 knockout Townes sickle (SSCKO) mice to investigate the role of calpain-1 in steady state and hypoxia/reoxygenation (H/R)-induced sickle platelet activation and aggregation, clot retraction, and pulmonary arterial hypertension. Using multi-electrode aggregometry, which measures platelet adhesion and aggregation in whole blood, we determined that steady state SSCKO mice exhibit significantly impaired PAR4-TRAP-stimulated platelet aggregation as compared to Townes sickle (SS) and humanized control (AA) mice. Interestingly, the H/R injury induced platelet hyperactivity in SS and SSCKO, but not AA mice, and partially rescued the aggregation defect in SSCKO mice. The PAR4-TRAP-stimulated GPIIb-IIIa (αIIb β3 ) integrin activation was normal in SSCKO platelets suggesting that an alternate mechanism mediates the impaired platelet aggregation in steady state SSCKO mice. Taken together, we provide the first evidence that calpain-1 regulates platelet hyperactivity in sickle mice, and may offer a viable pharmacological target to reduce platelet hyperactivity in SCD. Highlights: Gene knockout in sickle mice reveals a role for calpain-1 in platelet function. At steady state, calpain-1 is required for sickle cell platelet aggregation. Hypoxia/reoxygenation partly reduces reliance on calpain-1 for platelet aggregation.